Deteksi Citra CT Scan Paru-paru untuk Penentuan Luas dan Keliling dengan Metode Active Contour - Negoro, Wahyu Saptha; Azhar, Asbon Hendra; Destari, Ratih Adinda (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
Much research has been carried out on medical image processing by developing various methods of image processing. The research was carried out with the aim of improving image quality, so that it is easier to interpret and analyze images objectively. The same is true for CT scan images of the lungs, which are images in DICOM (Digital Imaging and Communications in Medicine) format which were researched using the Active Contour method to be able to segment the borders of the lungs and be able to calculate the size of their area and circumference more appropriate. There were 5 CT scan images of the lungs used in this research as examples of segmentation using the Active Contour method. The results obtained from detecting CT scan images of the lungs based on validation of the suitability of calculating the area and circumference of the lungs by doctors have an accuracy of 80%. Based on this research, it can be used as a medical reference for determining the size of the area on CT scan images of the lungs.